ANALISIS PENGARUH KUALITAS PRODUK, PROMOSI DAN DESAIN TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG DI KOTA AMBON - Walter Tabelessy (Soso-Q : Jurnal Manajemen, 2020)
This study aims to analyze the effect of product quality, promotion and design on the purchasing decisions of Samsung Smartphones in Ambon City. The population in this study is Samsung Smartphone consumers in Ambon. The sample used was 100 respondents with accidental sampling technique. Data collection techniques with questionnaires, while data analysis techniques using multiple linear regression analysis. From the F test results it is known that the regression model is feasible to measure the purchasing decisions of Samsung smartphones to consumers in Ambon City. Based on the results of multiple linear regression analysis of the t test, the results show that product quality, promotion and design have a significant effect on the purchasing decision of Samsung Ambon City Smartphones. Keywords: Product Quality, Promotion, Design, Purchasing Decisions